Role of water on mechanical properties of mud-stone - Prateep Duangduen; Onodera, T. F.; Campbell, K.V.; Brenner, R.P.; Government of the United Kingdom (Bangkok : Asian Institute of Technology, 1978)
The mudstones above and below the lignite bed from the Mae Mo Lignite Mining in Lampang province, Thailand were collected to study the role of water content on their mechanical properties in the undisturbed and remolded states. The physical properties of petrography, x-ray diffraction and scanning electron properties, water content, density and specific gravity were also determined. For the mechanical properties; the swelling, slake - durability, creep, unconfined compression, tension and direct shear were determined at dry, natural or optimum and saturated state of water content. The mudstone is composed of kaolinite, illite, feldspar and quartz. The arrangement of the flaky crystals is almost parallel to the bedding plane and compacted layer. The natural and saturated water contents of the undisturbed mudstone above and below lignite are 20.0 %, 29.6 % and 29.3 %, 40.1 % respectively while those of the remolded mudstone are 29.5 %, 41.3 % and 30.5 %, 43.1 % respectively. The dry, natural and saturated densities of the undisturbed mudstone above and under lignite are 1.58, 1.90 2.05 and 1.27, 1.64, 1.78 gm/cm3 respectively while those of the remolded mudstone are 1.34, 1.74, 1.89 and 1.20, 1.57, 1.72 gm/cm3 respectively. The grain specific gravities of the mudstone above and under lignite are 2.42 and 2.21 respectively. The effect of drying causes more swelling. The arrangement of flaky crystals parallel to bedding plane or compacted layer causes pronounced swelling in a direction perpendicular to the bedding or compaction plane. Anisotropy considerably influences swelling, modulus of elasticity, Poisson's ratio and tensile strength. The changing in bond and structure of the undisturbed mudstone by remolding causes larger swelling; higher durability; decreasing unconfined compressive strength, modulus of elasticity, tensile strength, shear strength, internal friction angle; increasing Poisson's ratio. The amount of flaky lignite layer containing in mudstone causes larger swelling and reduces strength of mudstone. All strength properties of the mudstone decrease with increasing water content.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology, 1978
Keywords: Rock mechanics